PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN MCDONALD'S AREA DEPOK - Fero Chinta; Risza Putri Elburdah (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to determine the effect of compensation and job satisfaction on employee productivity at McDonald's Depok Area, both partially and simultaneously. The method used is a quantitative method with descriptive and verificative approaches. The research population was all McDonald's Depok Area employees covering four outlets with a total sample of 94 respondents using saturated sampling technique. Data were collected through observation, questionnaires, and documentation. Analysis methods include validity test, reliability test, classical assumption test, simple and multiple linear regression analysis, Pearson and multiple correlation analysis, coefficient of determination test, and significance test (t test and F test). The results showed that partially compensation has a positive and significant effect on employee productivity with t count 5.601 > t table 1.662 and Sig. < 0.001 < 0.05 with Pearson correlation 0.504. Partially job satisfaction has a positive and significant effect on employee productivity with t count 10.779 > t table 1.662 and Sig. < 0.001 < 0.05 with Pearson correlation 0.747. Simultaneously compensation and job satisfaction have a positive and significant effect on employee productivity with F count 68.673 > F table 3.095 and Sig. < 0.001 < 0.05. The multiple linear regression equation Y = -5.778 + 0.218X₁ + 0.938X₂ with multiple correlation coefficient 0.776 and coefficient of determination 0.601 or 60.1% (Adjusted R² = 0.593 or 59.3%), indicating that compensation and job satisfaction simultaneously contribute 60.1% to McDonald's Depok Area employee productivity.